Everyman - Roth, Philip 1933-2018 (Houghton Mifflin, 2006)
A successful commercial artist with three very different ex-wives, a daughter who adores him, and two sons who despise him, the protagonist finds his confidence, sense of independence, and well-being undermined by an attack of illness in middle age.
Keywords: Commercial artists - New York (State) - New York - Fiction; Mortality - Fiction; Mann - Alter - Tod - Belletristische Darstellung; Aging -- Fiction; Jewish men -- Fiction; Fiktionale Darstellung; Domestic fiction - lcsh; Psychological fiction - lcsh